Severe amnestic syndrome due to theophylline toxicity. Issue 5 (5th May 2021) - Joyce, Eimear; Olszewska, Diana Angelika; Davy, Shane; Counihan, Timothy J
Abstract : We report a case of severe amnestic syndrome following theophylline overdose. A woman in her early 30s was admitted to hospital where she developed status epilepticus following an intentional overdose of theophylline and lansoprazole. She developed a profound acidosis and required intubation in the intensive care unit. Following extubation the patient was noted to have a severe amnestic syndrome with poor short-term memory. A work-up to exclude infectious, autoimmune and paraneoplastic causes for encephalitis was undertaken. Cerebrospinal fluid analysis was normal and autoimmune encephalitis titres were negative. Initial MRI brain imaging demonstrated hyperintensities of the mesial temporal lobes bilaterally. Follow-up imaging at 4 months identified further interval reduction but persistent hippocampal hyperintensities. Theophylline toxicity with corresponding amnestic syndrome and hippocampal hyperintensities has been rarely reported. We believe this case with persistent abnormal Montreal Cognitive Assessment Score at 12 months correlates with persistent hippocampal abnormalities seen on imaging.